Strategic continuous process improvement which quality tools to use, and when to use them - Plenert, Gerhard Johannes (McGraw-Hill, 2012)
This practical guide explains how to implement a strategic performance model and select and integrate appropriate metrics to acheive desired goals. -- from back cover.